2020
DOI: 10.1007/s10750-020-04330-x
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal patterns of fish assemblages in European boreal streams

Abstract: Fish assemblages are known to change from headwaters to river outlets. Still, our knowledge of this change is often approximate or sporadic. In this study, we quantified the average longitudinal change from a large electrofishing data set of boreal streams in Northern Europe. The average species richness increased from headwaters to medium-sized rivers but levelled off when reaching large rivers. Existence of some headwater specialist fish species, e.g. brook trout (Salvelinus fontinalis), was interpreted to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…Our study has management implications specifically in small streams, which are important for brown trout (Jonsson et al, 2001;Sutela et al, 2020;Vehanen et al, 2020). Survival during the juvenile stages is highly important for the growth of the brown trout populations (Elliott, 1994), and predation is one of the main drivers of fish community structure (Gebrekiros, 2016).…”
Section: Con Clus Ionsmentioning
confidence: 99%
“…Our study has management implications specifically in small streams, which are important for brown trout (Jonsson et al, 2001;Sutela et al, 2020;Vehanen et al, 2020). Survival during the juvenile stages is highly important for the growth of the brown trout populations (Elliott, 1994), and predation is one of the main drivers of fish community structure (Gebrekiros, 2016).…”
Section: Con Clus Ionsmentioning
confidence: 99%
“…Concerning our findings about weak relationships between geodiversity and diatom and macroinvertebrate and fish richness, it possibly shows that other environmental descriptors play a more important role than the richness of hydrogeomorphological features in shaping species richness. Indeed, freshwater species richness and endemism patterns are the result of climate, productivity and biogeographical history, so factors such as river connectivity, upstream barriers and isolation are likely to provide a better understanding of the distribution of fish species at the regional scale than local scale factors, such as hydromorphology or pollution (Griffiths et al, 2014; Oikonomou et al, 2014; Sutela et al, 2020). Previous works on freshwater fishes have shown that total species richness was also influenced by drainage characteristics and factors related to area, energy availability (i.e., net primary productivity) and climatic parameters (annual rainfall and average annual temperature) (Boll et al, 2016; Griffiths et al, 2014; Pelayo‐Villamil et al, 2015; Tedesco et al, 2017; Tisseuil et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For example, zonation concepts are used for description rather than explanation of longitudinal changes. Another shortcoming of zonation concepts is that fish zones may be defined according to the appearance of local indicator species, which limits their widespread application [65][66][67]. For the lacking explanation for the longitudinal fish composition change, two processes, involving species addition and species replacement have been proposed [23,29,31,66].…”
Section: Suggestions For Shortcomings In the Use Of Zonation Conceptsmentioning
confidence: 99%
“…To overcome the dependence on the occurrence of indicator species, zonation concepts can be refined by a new classification system (e.g., general biocoenotic terms and the intensity of human activities) [65][66][67]. In the Taizi basin, anthropogenic disturbances were the key drivers in shaping the longitudinal fish organization pattern.…”
Section: Suggestions For Shortcomings In the Use Of Zonation Conceptsmentioning
confidence: 99%